2005
DOI: 10.1177/0885066605280825
|View full text |Cite
|
Sign up to set email alerts
|

Linezolid-Associated Serotonin Syndrome After Concomitant Treatment With Citalopram and Mirtazepine in a Critically Ill Bone Marrow Transplant Recipient

Abstract: Linezolid was initially discovered as an antidepressant because of its effect on blocking intracellular metabolism of serotonin, norepinephrine, and other biogenic amines. As time passed, it was realized that linezolid possessed antibacterial activity, and linezolid has been developed and marketed as such. In medicine we are quick to categorize drugs into specific classes as a mechanism to recall indication and use. By classifying linezolid as an antibacterial, it is common to forget about its antidepressant r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 11 publications
(11 reference statements)
0
27
0
Order By: Relevance
“…In earlier case reports concurrent use of antipsychotics and antidepressants such as linezolid and mirtazapine or sertraline was reported to lead to a life-threatening state, the serotonin syndrome (16,17). Because linezolid can block the intracellular metabolism of amines, it can interact with agents acting on amines such as serotonin or noradrenalin in neuronal synapses and can induce a lethal serotonin syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…In earlier case reports concurrent use of antipsychotics and antidepressants such as linezolid and mirtazapine or sertraline was reported to lead to a life-threatening state, the serotonin syndrome (16,17). Because linezolid can block the intracellular metabolism of amines, it can interact with agents acting on amines such as serotonin or noradrenalin in neuronal synapses and can induce a lethal serotonin syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Aditionally, one study conducted in Peru showed that psychotherapy with adjunctive psychotropic medications in the anti‐TB treatment of patients with MDR‐TB resulted in improved treatment adherence, completion, and social rehabilitation compared to patients treated with anti‐TB treatment alone . Today, linezolid is an effective first‐line anti‐TB treatment that has been reported as a monoamine oxidase inhibitor with antidepressant properties …”
Section: Association Between Depression and Tbmentioning
confidence: 99%
“…Linezolid is a totally synthetic compound that was initially synthesized as a reversible MAO inhibitor class antidepressant [29]. …”
Section: Casementioning
confidence: 99%
“…Interactions have been found with the selective serotonin reuptake inhibitors (SSRIs) as citalopram [29, 3339], escitalopram [34], paroxetine [40], fluoxetine [41, 42], sertraline [4345], with tryptophan, a precursor of serotonin [46], with noradrenaline and specific serotonergic agents (NaSSA) as mirtazapine [29], with serotonin 2 antagonist/reuptake inhibitor (SARI) as trazodone [36], the azapirone category anxiolytic buspirone that is a serotonin 1A partial agonist and serotonin stabilizer [47], the dual serotonin and noradrenaline reuptake inhibitors (SNRIs) as the antidepressants venlafaxine [36, 4851] and duloxetine [52], and the tricyclic antidepressant (TCA) imipramine [49]. Although amitriptyline [14, 5356] and fentanyl [5764] have been both involved in serotonin syndrome, no case has been reported involving their combination.…”
Section: Casementioning
confidence: 99%